(untitled) (Journal of Student Affairs in Africa, 2025)
The transition from high school to university is widely recognized as challenging for many students, but was especially challenging for students who experienced almost two years of disrupted schooling during the COVID-19 pandemic. Pre-pandemic, the University of the Witwatersrand (Wits) ran a one-week first year orientation programme. In mid-2021, as the severity of the pandemic was easing, it was clear that new students would need more than one week to adjust not just to university life but also to in-person interactions. As Academic Affairs and Student Affairs leaders we therefore undertook to design and implement an extended, integrated academic and student life orientation programme that would be compulsory for all 6500 new first year students in 2022 called Gateway to Success (GTS). Rapidly changing circumstances meant we had only four months to do this. In this paper we discuss the design of GTS and explain how we could plan it so quickly by utilizing a networking approach combined with a modified agile project management approach we had been developing since 2019. We then provide student evaluation results from 2022, and discuss how GTS was modified in 2023 when pandemic-related restrictions were lifted. We conclude with a discussion of how GTS has been embedded in university structures and processes and contributes to our institutional commitment to student success.